Analysis of Value Added Tax Compliance and Tax Reporting (A Study At PT. Karya Lancar Mandiri Dinamika) - Bucek Jalu Prasetyo Arjuna; Bakhtiar Abbas; Massayu Anastasya (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
This study aims to analyze tax compliance and tax reporting of Value Added Tax. This study was conducted at PT. Karya Lancar Mandiri Dinamika. The Data collection techniques used are documentation and interview data from PT. Karya Lancar Mandiri Dinamika to obtain the required information. Based on the results of the study indicate that that compliance and reporting of Value Added Tax at PT. Karya Lancar Mandiri Dinamika is in accordance with Law Number 42 of 2009 concerning VAT and PPnBm both in terms of calculation and reporting of VAT Periodic Returns.